ANALISIS PRODUKTIVITAS KERJA REPARASI KAPAL AWB KINGFISHER 4565 GT TERHADAP EFEKTIVITAS MANAJEMEN WAKTU MENGGUNAKAN MODEL OBJECTIVE MATRIX (OMAX) - Muhammad Marcell Raymus Abdurrahman, (2021)
Ships have been a mode of transportation of goods and people since ancient times. Every ship that is built, of course, requires a maintenance schedule to maintain the productivity and safety of the ship. In Indonesia, there are many shipyards that provide several types of facilities that can be used to carry out ship maintenance. One of them, is that ship repair is the type of ship maintenance that is most often carried out in shipyards. This study aims to determine the productivity criteria and indicators of shipyard work, measure the level of productivity, determine the factors that influence the increase in productivity on the effectiveness of time management, and identify the initial steps to increase productivity at PT. Kodja Bahari Dock & Shipping especially in Shipyard 1 Jakarta. The method used in this research is a case study method with productivity measurement using the OMAX model.